2020
DOI: 10.1155/2020/6719301
|View full text |Cite
|
Sign up to set email alerts
|

Is Extra Virgin Olive Oil an Ally for Women’s and Men’s Cardiovascular Health?

Abstract: Noncommunicable diseases are long-lasting and slowly progressive and are the leading causes of death and disability. They include cardiovascular diseases (CVD) and diabetes mellitus (DM) that are rising worldwide, with CVD being the leading cause of death in developed countries. Thus, there is a need to find new preventive and therapeutic approaches. Polyphenols seem to have cardioprotective properties; among them, polyphenols and/or minor polar compounds of extra virgin olive oil (EVOO) are attracting special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 391 publications
(393 reference statements)
1
11
0
1
Order By: Relevance
“…Indeed, it is well-known that age, excess weight and visceral adiposity can contribute to increase risks of hypertriglyceridemia, hypercholesterolemia, diabetes and hypertension (34). In addition, our study confirms that even in Mediterranean countries, especially in southern Italy, where EVOO consumption is a common everyday practice, there is better control of LDL cholesterol levels in subjects who follow this custom more closely (35,36).…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, it is well-known that age, excess weight and visceral adiposity can contribute to increase risks of hypertriglyceridemia, hypercholesterolemia, diabetes and hypertension (34). In addition, our study confirms that even in Mediterranean countries, especially in southern Italy, where EVOO consumption is a common everyday practice, there is better control of LDL cholesterol levels in subjects who follow this custom more closely (35,36).…”
Section: Discussionsupporting
confidence: 81%
“…Extensive scientific research has demonstrated that daily consumption of EVOO is associated with numerous health benefits and a low-risk onset of chronic-degenerative non-communicable diseases (CDNCDs) [ 3 ]. Significant effects on the prevention of cancer, diabetes mellitus, chronic kidney disease (CKD), metabolic syndrome, obesity, arterial hypertension, neurological and cardiovascular diseases were reported [ 4 , 5 , 6 , 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…26 In this study, the authors did not report a thorough characterization of the formed metabolites, nor was the interpretation validated. 27 Although analysis of oleocanthal either in olive oil or as a purified compound has been done using liquid chromatography (LC) separation coupled with ultraviolet or mass spectrometry (MS) detection, 28−34 and by quantitative 1 H NMR, 35 there are no studies addressing the detection and quantification of oleocanthal in biological fluids such as culture media, human or animal plasma, or tissues.…”
mentioning
confidence: 99%